Measurement of the top quark mass using proton-proton data at ${\sqrt{(s)}}$ = 7 and 8 TeV - CMS collaboration (2309 authors) (2016)
A new set of measurements of the top quark mass are presented, based on the proton-proton data recorded by the CMS experiment at the LHC at s=8  TeV corresponding to a luminosity of 19.7  fb-1. The top quark mass is measured using the lepton+jets, all-jets and dilepton decay channels, giving values of 172.35±0.16(stat)±0.48(syst)  GeV, 172.32±0.25(stat)±0.59(syst)  GeV, and 172.82±0.19(stat)±1.22(syst)  GeV, respectively. When combined with the published CMS results at s=7  TeV, they provide a top quark mass measurement of 172.44±0.13(stat)±0.47(syst)  GeV. The top quark mass is also studied as a function of the event kinematical properties in the lepton+jets decay channel. No indications of a kinematic bias are observed and the collision data are consistent with a range of predictions from current theoretical models of tt¯ production.